BIOLEACHING PROCESS OF RARE EARTH ELEMENTS FROM RED MUD WASTE ALUMINA PURIFICATION PROCESS IN TAYAN, WEST KALIMANTAN, USING BACILLUS ZANTHOXYLI STRAIN SKC/VA-2 - Minzikrina Masbar Rus, Aisyah
Residual bauxite or red mud is the residue from the Bayer process that refines bauxite ore into alumina. Red mud contains valuable metals such as Fe, Al, Ti and rare earth elements (REE) such as Ce, Sc, Y, Nd and Gd, which make this waste toxic and can cause environmental pollution. The metal recovery from red mud waste is usually extracted by the hydrometallurgical process. As an alternative to the hydrometallurgical process, a process was developed to extract metals from red mud using the biohydrometallurgical process. Biohydrometallurgy is an ecological process which requires low energy and can be used to extract metals at very low concentrations. This study examines the recovery of REE from the bauxite ore processing industry in Tayan, West Kalimantan by the bioleaching method using Bacillus zanthoxyli strain SKC/VA-2 as a leaching agent. A series of bioleaching experiments were conducted to study the effect of pulp density and bioleaching medium on the extraction percentage of REE. The bioleaching process was conducted at room temperature (± 25°C), medium pH 1, with red mud particle size -200# +270# (-75 ?m +53 ?m), 10% (v/v) bacterial inoculum and 180 rpm rotary shaker speed for 7 days. Bioleaching experiments were conducted at 2% and 5% pulp density and four medium variations as follows: 4 g/L molasses, 5 g/L sulfur addition, 5 g/L sulfur and 2.8 g/L pyrite addition and 10 g/L sulfur and 5.6 g/L pyrite addition. Percentage of REE extraction as a function of time at various bioleaching conditions was periodically determined by ICP-MS (inductively coupled plasma-mass spectrometry) analysis. Based on the experimental results, the best bioleaching process parameters were 2% pulp density variation in Medium 2 (molasse 4 g/L, sulfur 5 g/L) with REE extraction percentage of 98,11% Tb; 98,41% Gd; 95,0% Lu; 78,76% Nd; 45,03% La; 41,99% Ce; 38,05% Y. Increasing pulp density causes a decrease in the percent of REE extraction due to cell damage, decreased O2 concentration and agitation effects. This is due to the increased solution of viscosity and inhibited bacterial growth due to the increased metal concentration in the bioleaching medium which is toxic. The decrease in the percent of REE extraction in the medium without the addition of sulfur and pyrite is due to bacteria due to the lack of energy supply. Sulfur acts as a source of sulfide compounds needed as electron donors for bacterial metabolism while pyrite acts as a source of Fe2+ to increase the redox potential value in bioleaching